Pathological investigation of local infectious laryngotracheitis virus isolated from layers on broiler Chicks (Texas Journal of Agriculture and Biological Sciences, 2022)
In this study, The PCR molecular test was performed on samples gathered from local laying farms that exhibited symptoms of ILT. With the wild strain, ILTV was positive, and subsequently, AI, ND, and IB were tested and all negative findings were found. ECE was inoculated with the prepared positive sample using the CAM method for three separate passages. PCR testing and viral titration, in the same manner, was carried out again once the cytopathic impact occurred. The EID50 is the fourth dilution. An ELISA test for maternal ABs was performed on four groups of broiler chickens (A, B, C, and D), each group containing 50 birds, and an experimental infection was made for three groups, with group D remaining as control negative. Group A was infected at one day, Group B at 15 days, and Group C at 30 days, clinical signs and pathological lesions, both macroscopic and microscopic in nature, were observed. After clinical indicators, affected groups performed the histopathological test. And then all groups had 3 ELISA tests at 1, 2, and 3 weeks following infection. The experiment indicated that group A was the least affected. Group B was more impacted than A, whereas group C had more clinical indications and mortalities, indicating that broiler chickens of all ages are vulnerable to infection, although maternal immunity may offer some protection for at most two weeks. This research was done to provide information to the scientific library of broiler chickens infected with ILT, which has been more investigated in laying hens and breeders.